Pengaruh Dana Pihak Ketiga (DPK), Loan to Deposit Ratio (LDR) dan Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Return on Assets (ROA) Bank Umum Persero di Indonesia Periode Tahun 2019-2023 - Oktariani, Shanty; Meliza, Juli (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to determine the influence of Third Party Funds (DPK), Loan to Deposit Ratio (LDR) and Operational Costs, Operational Income (BOPO) on Return on Assets (ROA) at Persero Commercial Banks in Indonesia. This research uses multiple linear regression methods and uses the SPSS analysis tool. The results of this research show that simultaneously the variables Third Party Funds (DPK), Loan to Deposit Ratio (LDR) and Operating Costs Operating Income (BOPO) have an effect on Return on Assets (ROA). Partially, the Third Party Funds (DPK) and Loan to Deposit Ratio (LDR) variables do not have a significant effect, Operational Costs and Operational Income (BOPO) have a significant negative effect on Return on Assets (ROA).